2015
DOI: 10.1111/jbfa.12170
|View full text |Cite
|
Sign up to set email alerts
|

Governance Structure and Firm Performance in Private Family Firms

Abstract: Abstract:Although a large proportion of firms are family owned and most family firms are private, our understanding of private family firms is limited. Using confidential information on family relationships between board members, CEOs, and shareholders, this is the first study to provide large-scale evidence on the association between governance structure and firm performance in family-controlled private firms. Our sample is unique as it covers almost all private limited liability firms in Norway, spans 11 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 92 publications
(152 reference statements)
3
34
0
1
Order By: Relevance
“…Consistent with Che and Langli (2015), considered a sample of Norwegian firms and found that smaller board effectively contributes to firm performance. Kamazima, Mathenge, and Ngui (2017), also explored the negative effect of board size on firm performance.…”
Section: Literature Review Board Sizementioning
confidence: 80%
“…Consistent with Che and Langli (2015), considered a sample of Norwegian firms and found that smaller board effectively contributes to firm performance. Kamazima, Mathenge, and Ngui (2017), also explored the negative effect of board size on firm performance.…”
Section: Literature Review Board Sizementioning
confidence: 80%
“…9 We thank the reviewer for the suggestion of using attributes of family CEOs. 10 The board structure might be less important than the ownership structure for firm performance in private family firms (Che and Langli 2015). 11 Note that this is different from CEO duality, which refers to the case that the CEO and the chair of the board are the same person.…”
Section: Control Variablesmentioning
confidence: 97%
“…The private sector have more clearly defined property rights rather than the public sector, and thus, incentives for seeking profits by private owners which then leads to more effective management performance monitoring (Alchian 1965;McCormick and Meiners 1988). Specifically because a close linkage exists between the wealth of private controllers and the welfare of the firm, they focus more on cost minimization while maximization profits than governments (Che and Langli 2015).…”
Section: Type Of Ownermentioning
confidence: 99%